NEW CONCEPT OF HUNGARIAN ROBOTIC TELESCOPES - Hegedus, T.; Kiss, Z.; Biro, B.; Jager, Z. (Одеські астрономічні публікації, 2007)
As the result of a longer innovation of a few Hungarian opto-mechanical and electronic small companies, a concept of fully robotic mounts has been formed some years ago. There are lots of Hungarian Automated Telescopes over the world (in Arizona, South Korea, Izrael and atop Mauna Kea, just below the famous Keck domes). These are cited as HAT telescopes (Bakos et al. 2002), and served thousands of large-frame time-series CCD images since 2004, and the working team found already 6 exoplanets, and a number of new variable stars, etc... The newest idea was to build a more robust robotic mount, hosting larger optics (D > 50 cm) for achieving much fainter celestial objects, than the HAT series (they are operating with Nikon teleobjective lenses) on a still relatively wide celestial area. The very first sample model is the BART-1, a 50cm f/6 telescope.